Peran Sholat dalam Pembentukan Karakter dan Etika dalam Kehidupan Sehari-Hari - Hafizh Rafid Hardian; Reifan Mezquita Aziez; Anis Nada Khairin; Andriyani Andriyani; Raghib Filhaq (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
This study discusses the role of prayer in shaping character and daily ethics as one of the main pillars of Islamic teachings. Prayer is not merely a ritual act of worship but also serves as a means of spiritual and moral education and shapes the overall personality of Muslims. This study uses a literature review method by examining various sources such as books, journals, and scientific articles relevant to Google Scholar from 2020 to 2025, sourced from 20 Indonesian-language journals and 5 English-language journals. Based on this background, prayer plays an important role in instilling values of discipline, responsibility, sincerity, patience, and self-reflection, which contribute to the formation of an individual's character and integrity. In addition, prayer also serves as the foundation of social ethics by fostering honesty, justice, empathy, politeness, and solidarity in social interactions. There is also congregational prayer, which, when performed, can strengthen the values of togetherness, brotherhood, and social concern, which are the foundations of a harmonious social life. Research shows that consistent and solemn prayer practices can control desires, prevent immoral and evil deeds, and provide mental and spiritual balance for the practitioner. Thus, prayer is an important instrument in the moral and spiritual development of Muslims and is relevant in facing modern challenges such as stress and social ethical degradation.